Faith development theory revisited: the religious styles perspective - Streib, Heinz (The international journal for the psychology of religion, 2001)
Focusing on Fowler's (1981) faith development theory (FDT), this article presents a modification of structural-developmental theory of religion. The primacy of cognitive development as motor and guideline of religious development is called into question. The new model, the typology of religious styles, is aimed at accounting more fully for the life-history- and life-world-relatedness of religion, at its principal interactive, interpersonal origin and shape. Thus the phenomenologists Merleau-Ponty (1962, 1988) and Ricoeur (1985/1988, 1990/1992) who provide philosophical perspectives, Noam's (1985, 1988a, 1988b, 1988c, 1990) developmental perspective, which is based on interpersonality, as well as Rizzuto's (1979, 1991) view of the psychodynamic development of religion, play a significant role for the reformulation. An overview of styles is described and illustrated in a figure. References to results of empirical research are included, and an explanation of fundamentalism is outlined that follows from the religious styles perspective.